This equation is a form of exponential decay because the number being raised the power is a fraction, and whenever a fraction is raised to a positive power, the result decreases. In order to find the y-intercept, plug in zero as the x and find y. Whenever a number is raised to the zero power, the answer is always one.

\(\displaystyle{y}={0.6}{\left(\frac{{1}}{{10}}\right)}^{{x}},{x}={0},{y}={0.6}{\left(\frac{{1}}{{10}}\right)}^{{0}}={0.6}\)

\(\displaystyle{y}={0.6}{\left(\frac{{1}}{{10}}\right)}^{{x}},{x}={0},{y}={0.6}{\left(\frac{{1}}{{10}}\right)}^{{0}}={0.6}\)